Assessing habitat suitability and habitat fragmentation for endangered Siberian cranes in Poyang Lake region, China - Zhengtao Zhu (Elsevier, 2021)
Poyang Lake is located in the middle and lower reaches of the Yangtze River in China. It is the most important wintering area for the endangered Siberian cranes. Identifying the scale characteristics of habitat selection for Siberian cranes is essential for habitat conservation. In this study, a habitat suitability index (HSI) model based on multiscale habitat features was developed to assess the distribution and fragmentation degree of the suitable habitat for Siberian cranes before and after the construction of the proposed Poyang Lake Hydraulic Project (PLHP). The habitat of the entire lake area was divided into four ranks on the basis of HSI values. 2D shallow-water equations (SWEs), combined with remote sensing and geographic information system technology, were utilized to determine the key habitat features. Results indicated that the established HSI model could effectively recognize the potentially suitable habitats for Siberian cranes in Poyang Lake. The highly suitable habitat in the wet year was larger than that in the dry year, and the complexity of patch shapes and patch fragmentation increased. The influence of the PLHP on the suitable habitat for cranes mainly depended on its regulated water level, and this project could promote the formation and reduce the fragmentation degree of the suitable habitat under a properly regulated water level in the dry year. However, a higher regulated water level may cause a considerable negative impact on the distribution of suitable habitats in both years. This study provided a quantitative method to evaluate the potentially suitable habitats for Siberian cranes, and it could serve as a reference for the water level management of the proposed PLHP.